TDP-43 and Limbic-Predominant Age-Related TDP-43 Encephalopathy - Zhang, Lumi; Chen, Yi; Liu, Min; Wang, Yunyun; Peng, Guoping (Frontiers in Aging Neuroscience, 2020)
Through a number of extensive autopsy, biomarker, and genomics studies, researchers have recently defined a novel type of dementia known as limbic-predominant age-related TDP-43 encephalopathy (LATE). LATE is perhaps best characterized by the presence of hyperphosphorylated TDP-43, which plays multi-functional roles through interactions with DNA and RNA, leading to significant alterations in the transcription and translation of particular genes. As individuals of advanced age represent a rapidly growing demographic group globally, there is a steadily increasing rate of LATE incidence that has to date received insufficient recognition despite its serious implications for public health. TDP-43 is the common pathology of various age-related dementia, therefore, it may be a potential and promising therapeutic target for such diseases. In the present review, we discuss the pathways regulating TDP-43 expression, metabolism, and disease activity in order to better understand the link between TDP-43 proteinopathy and LATE at the genetic, pathological, and clinical levels.